Evaluation of encapsulated proteolytic enzymes from white shrimp (Litopenaeus vannamei) hepatopancreas for potential supplementation in tilapia feed - Pablo Sergio Osuna-Amarillas; Kenia Yamileth Medina-Rivera; Martha Elisa Rivas-Vega; Francisco Javier Cinco-Moroyoqui; Octavio Cota-Arriola; Wilfrido Torres-Arriola; Norma Aurora Stephens-Camacho; Anselmo Miranda-Baeza (Food Chemistry Advances)
This study aimed to evaluate the extraction, semi-purification, encapsulation, and release of proteolytic enzymes from the hepatopancreas of white shrimp (Litopenaeus vannamei) for potential inclusion in pelleted feed for tilapia. Proteases were extracted using hydrophobic interaction chromatography, yielding a semi-purified shrimp hepatopancreas extract (SPESH). SDS-PAGE analysis identified four distinct protein bands and the optimal conditions for enzyme activity were determined across a range of temperatures (0–100 °C) and pH levels (4–11). Inhibition assays revealed the presence of serine proteases, primarily trypsin-type enzymes, alongside aspartic and cysteine proteases. SPESH exhibited maximum proteolytic activity at 40 °C and pH 9. Proteolytic activity from the sodium alginate capsules was observed 30 min after encapsulation release testing, with a stable trend up to 120 min. Over the 0–16 days storage period, the proteolytic activity of capsules incubated for 60 min (36.3 ± 2.80 to 38.4 ± 1.21 AU) and 120 min (45.4 ± 1.40 to 47.8 ± 0.28 AU) prevailed stable with no significant differences (P < 0.05), indicating consistent enzyme release. The encapsulation method allowed a gradual release of enzymes at pH conditions representative of the Nile tilapia (Oreochromis niloticus) digestive tract, supporting its potential for controlled delivery and enzyme supplementation in feed.